SCREENING BAKTERI PENGHAMBAT UNTUK BAKTERI PENYEBAB PENYAKIT PADA BUDIDAYA IKAN KERAPU DARI PERAIRAN BANTEN DAN LAMPUNG - Hatmanti, Ariani; Nuchsin, Ruyitno; Dewi, Julinasari (UI Scholars Hub, 2009)
Screening for Inhibitor Bakteri for Pathogenic Bacteria in Groupers Culture in Banten and Lampung Waters. A research about screening of inhibitor bacteria for pathogenic bacteria in grouper culture was done during 2005 in Marine Microbiology Laboratory, Research Center for Oceanography LIPI. Inhibition test was done using paper disc method for three isolates of pathogenic bacteria in his research, they were: Vibrio harveyii, 9.2/Luka/TSA and 8.2/Luka/TSA. The result shows that from 39 isolates of inhibitor bacteria from Banten and 27 isolates of inhibitor bacteria from Lampung only two isolates showed inhibition effect to the growth of three isolates of pathogenic bacteria. found inhibit the three strains of pathogenic bacteria mentioned above. The two isolates of inhibitor bacteria were 9L/AL-4/KNG/BLC/BOKN/BJN and 5L/AL-4/KNG/BJN, which were isolated from Bojonegara, Banten.